Inversor híbrido de cinco níveis: estudo, operação e controle da tensão do capacitor flutuante - Santos, Thais Lima (2024)
This work proposes the analysis and control of a five-level DC/AC inverter with a reduced number of power switches. The considered hybrid topology is the result of combining a threelevel Flying Capacitor (FC) inverter with a Neutral-Point Clamped (NPC) inverter. The number of levels in the FC converter is increased to four by changing the voltage ratio between the DC bus and the voltage at the floating capacitor terminals. The reduction in the number of components leads to a decrease not only in the number of auxiliary and control circuits but also in the converter's volume compared to conventional topologies. In this type of configuration, it is necessary to control the voltage at the floating capacitor terminals to one-fourth of the bus voltage to ensure proper operation. Thus, a voltage control technique is presented, aided by Pulse-Width Modulation (PWM), which allows for the regulation of this voltage and the generation of the necessary levels for the inverter's operation. To enable the inverter to be powered by a low voltage, a configuration is proposed where the inverter is integrated with a DC-DC voltage boost converter with a reduced number of capacitors in the bus compared to a conventional five-level FC circuit. An analysis of conduction and switching losses in semiconductors, as well as stress analysis of voltage, current, and temperature, along with total harmonic distortion in the generated currents and voltages, is presented to evaluate the topology's performance. Simulation results validate the operating principle of the converters, the PWM techniques applied to the converter, and the employed control strategies.